'Hidden Landscape Characterisation': Some Thoughts on the Relationship of HLC to Archaeological Data. (2nd July 2020) - Last, Jonathan
ABSTRACT: In 2009 the ninth annual English Heritage Characterisation Seminar addressed the subject of 'Hiddenscapes', with the aim of looking at how to apply an Historic Landscape Characterisation (HLC) approach to the less accessible archaeological layers of the historic landscape. This reflected the growing availability of large-scale digital datasets from aerial investigation and mapping, geophysics and excavation, alongside the recognition that too often the archaeological resource was treated as a series of discrete sites. Over a decade on from that seminar, however, archaeologists studying the prehistoric and Roman periods in England still make relatively little use of characterisation. At the same time, various academic projects have analysed large-scale archaeological data for these periods in other ways. It is therefore timely to reconsider the potential contribution of the HLC approach to the development of methods of characterising the buried archaeological landscape. This article considers the relationship between HLC and archaeological data and outlines a possible approach to mapping the character of the archaeological record.